Multi-stage model for the release of potassium in single particle biomass combustion. (15th November 2020) - Anca-Couce, Andrés; Sommersacher, Peter; Hochenauer, Christoph; Scharler, Robert
Highlights: Model for K release during pyrolysis, KCl evaporation and carbonate dissociation. Validated with single particle experiments with different fuels and temperatures. Correct prediction of online K release at different stages and final release. Abstract: The release of potassium during biomass combustion leads to several problems as the emissions of particle matter or formation of deposits. K release is mainly described in literature in a qualitative way and this work aims to develop a simplified model to quantitatively describe it at different stages. The proposed model has 4 reactions and 5 solid species, describing K release in 3 steps; during pyrolysis, KCl evaporation and carbonate dissociation. This release model is coupled into a single particle model and successfully validated with experiments conducted in a single particle reactor with spruce, straw and Miscanthus pellets at different temperatures. The model employs same kinetic parameters for the reactions in all cases, while different product compositions of the reactions are employed for each fuel, which is attributed to differences in composition. The proposed model correctly predicts the online release at different stages during conversion as well as the final release for each case.